Biomimetic Approach to Stimulate Osteogenesis on Titanium Implant Surfaces Using Fibronectin Derived Oligopeptide - Cho, Young-Dan; Kim, Sung-Jun; Bae, Han-Sol; Yoon, Won-Joon; Kim, Kyung-Hwa; Ryoo, Hyun-Mo; Seol, Yang-Jo; Lee, Yong-Moo; Rhyu, In-Chul; Ku, Young (Current Pharmaceutical Design, 2016)
Our previous studies demonstrated that a recombinant fibronectin (FN)-derived oligopeptide that we named F20 stimulated osteoblast adhesion, proliferation, and differentiation in vitro and in vivo. In the present study, we used a synthetic oligopeptide and investigated the osteogenic potential of F20 coating on titanium discs, to stimulate superior osseointegration for dental implant surface modification. Surface characteristic analysis of titanium was performed by confocal laser scanning microscopy (CLSM) observation. Synthetic F20 was coated onto the machined or SLA titanium discs by an adsorption procedure. ST2 cells were seeded on the titanium discs. We evaluated cell adhesion with SEM and CLSM observation, cell proliferation with picogreen assay, and osteoblast differentiation with real-time PCR, ALP activity assay, immunoblot assay and ALP staining. FITC-labeled F20 coating on the discs was detected by fluorescence, showing good F20 adsorption and different coating patterns according to the surface roughness. In the SEM and CLSM observations, cells were well attached on the machined surface and greater stress fiber formation was seen on discs coated with F20 than on other discs. F20 stimulated cellular proliferation, as well as osteoblast differentiation through the extracellular signalregulated kinase (Erk) signaling pathway. These cellular responses to F20 were slightly better on the machined titanium surface than the SLA surface. These results suggest that F20 promotes osteogenesis through the Erk pathway and is a suitable biomolecule for surface modification of dental implants for improved osseointegration.
Keywords: osteoblast differentiation